1.61 T-cells expressing TLR4 and CXCR4 are associated with an RA diagnostic in early inflammatory arthritis. (31st January 2014) - Parmar, R; Burska, Agata; Emery, P; Mellado, Mario; Sacre, Sandra; Ponchel, F
Abstract : Background: Biomarkers for the early diagnosis of RA are still needed despite the improvement brought about by ACR/EULAR-2010 criteria which include the ACPA biomarker. T-cell subset dys-regulation was shown to occur early in the RA disease continuum (Blood, 2002), to predict response to MTX (ARD, 2013) and safe discontinuation of biological when in clinical remission (ARD 2010). The aim of the current study is to determine whether T-cell subset phenotyping adding novel cell surface markers for TLR2, TLR4, IL-6R and 4 chemokine receptors (CCR3, CXCR4 CCR5 and CCR6) can discriminate between patients who are clearly RA from those with other (inflammatory) rheumatic diseases in an early arthritis clinic. Methods: 46 patients with <12 months IA were enrolled; age, CRP, joint counts, symptom duration, SE and ACPA were recorded. 6-8 colour flowcytometry was performed using standard protocols. 95 healthy controls (HC) were included to calculate age-corrected naïve cell frequency. Results: 23 of the 46 patients were diagnosed with RA. 9 had undifferentiated arthritis and 14 other rheumatic diseases (AS, SPA, gout and self-limiting). Not surprisingly, as part of the EULAR-2010 criteria, ACPA positivity (P<0.0001), CRP (P = 0.004) and swollen joint count (P = 0.003) were associated with RA. Naïve CD4+ T-cells tended to be reduced (p = 0.093) in RA and reached significance when RA and UA were compared to other diagnosis (p = 0.008). TLR4 expression was increased in RA (p = 0.100) and again significant in RA+ UA (P = 0.038). CXCR4 expression appeared increased in RA but a number of outliers reduced significance. CXCR4 expression was then analysed in relation with other chemokine receptors. The number of subset generated prevented classic statistical analysis so we used a clustering software which separated 2 groups of patients, one being associated with RA (p = 0.070) and ACPA-positivity (P = 0.072). Clustering was driven by increased CD4+ T-cell subsets positive for CXCR4 and expressing CCR5, CCR6 or IL-6R. This group was clearly associated with RA as well as ACPA-positivity. The second group was also characterised by increased CXCR4+ but on CD8+ T-cells with expression of CCR5, CCR6 or IL-6R and included mixed RA (mostly ACPA-negative) and non-RA patients. Conclusion: There are clear T-cell related immunological differences in patients with RA: loss of naïve T-cell, increased TLR4 + and combination of chemokine expression on CD4+ T-cell. We will therefore need to evaluate these biomarkers in larger number of patients with a high risk of progression towards RA to establish their definite value.